Absence of PEXEL-Dependent Protein Export in Plasmodium Liver Stages Cannot Be Restored by Gain of the HSP101 Protein Translocon ATPase - Kreutzfeld, Oriana; Grützke, Josephine; Ingmundson, Alyssa; Müller, Katja; Matuschewski, Kai (Frontiers in Genetics, 2021)
Host cell remodeling is critical for successful Plasmodium replication inside erythrocytes and achieved by targeted export of parasite-encoded proteins. In contrast, during liver infection the malarial parasite appears to avoid protein export, perhaps to limit exposure of parasite antigens by infected liver cells. HSP101, the force-generating ATPase of the protein translocon of exported proteins (PTEX) is the only component that is switched off during early liver infection. Here, we generated transgenic Plasmodium berghei parasite lines that restore liver stage expression of HSP101. HSP101 expression in infected hepatocytes was achieved by swapping the endogenous promoter with the ptex150 promoter and by inserting an additional copy under the control of the elongation 1 alpha (ef1α) promoter. Both promoters drive constitutive and, hence, also pre-erythrocytic expression. Transgenic parasites were able to complete the life cycle, but failed to export PEXEL-proteins in early liver stages. Our results suggest that PTEX-dependent early liver stage export cannot be restored by addition of HSP101, indicative of alternative export complexes or other functions of the PTEX core complex during liver infection.